Hidroformilação catalisada por complexos de cobalto e ródio: valorização de substratos biorrenováveis - Camilla Santos Bolsoni (2023)
The consumption of fragrance products is increasing every year, mainly due to their presence in society's daily life. These products are often essential and will not stop being used on a daily basis. It is through the hydroformylation process that various components of these products are obtained, especially those that impart aroma, such as aldehydes. In order to develop the process in question, studies were carried out on the use of cobalt as a catalyst in terpene hydroformylation reactions, using phosphine oxide as promoter. Another process studied was the hydroformylation catalyzed by rhodium complexes of linalool acetate, which is an ester with one double bond C-C terminal and one trisubstituted. This process presents high regioselectivity, leading to the exclusive formation of linear aldehyde. As a secondary product, diene is also formed (two stereoisomers), resulting from the hydrogenation/deacetoxylation of linalool acetate through the formation of the rhodium π-allyl complex as an intermediate. A study of the effects of the reaction conditions was carried out in order to find a more active, stable, and selective system. To this end, variations in pressure, temperature, P/Rh ratio, nature of the ligand, and solvent were carried out. The system proved to be more active and selective using triphenylphosphine and it is essential to optimize the P/Rh ratio for the system to increase the selectivity of the hydroformylation product in relation to the dienes. In addition, in order to replace solvent toluene, studies were carried out with green solvents such as ethanol and anisole. Among these, anisole proved to be the most promising for hydroformylation, given its contribution to aldehydo chemoselectivity, as well as greater reaction speed. The process developed proved to be promising for obtaining aldehydes from biorenewable olefins, especially in terms of the regio- chemoselectivity of the system, as well as the organoleptics properties of the product being pleasant for future use in fragrances.